Curriculum Proposal for a Bachelor’s in Mandarin - Vargas Barquero, Vivian (2018)
This article analyzes and discusses alternatives for the design of a curriculum for the teaching of Mandarin, from a Costa Rican academic perspective. Due to the increasing importance of bilateral political, commercial and cultural relations with China, the relevance of promoting the design of a bachelor’s degree in Mandarin, as one of the programs offered by the Universidad Nacional (Costa Rica), is highlighted. For this purpose, the process carried out to initiate the proposal is described, including a detailed report of the results of surveys among the target sector. In addition, various recommendations are given, in pedagogical, logistical and institutional matters in general.